The Role of Gut Barrier Dysfunction and Microbiome Dysbiosis in Colorectal Cancer Development - Genua, Flavia; Raghunathan, Vedhika; Jenab, Mazda; Gallagher, William M.; Hughes, David J. (Frontiers in Oncology, 2021)
Accumulating evidence indicates that breakdown of the protective mucosal barrier of the gut plays a role in colorectal cancer (CRC) development. Inflammation and oxidative stress in the colonic epithelium are thought to be involved in CRC development and the breakdown of the integrity of the colonic barrier might contribute to increase the exposure of colonocytes to toxins from the milieu, enhancing inflammatory processes and release of Reactive Oxygen Species (ROS). The aetiological importance of the gut microbiome and its composition – influenced by consumption of processed meats, red meats and alcoholic drinks, smoking, physical inactivity, obesity - in CRC development is also increasingly being recognized. The gut microbiome has diverse roles, such as in nutrient metabolism and immune modulation. However, microbial encroachment towards the colonic epithelium may promote inflammation and oxidative stress and even translocation of species across the colonic lumen. Recent research suggests that factors that modify the above mechanisms, e.g., obesity and Western diet, also alter gut microbiota, degrade the integrity of the gut protective barrier, and expose colonocytes to toxins from the colonic milieu. However, it remains unclear how obesity, lifestyle and metabolic factors contribute to gut-barrier integrity, leading to metabolic disturbance and potentially to CRC development. This review will discuss the interactive roles of gut-barrier dysfunction, microbiome dysbiosis, and exposure to endogenous toxins as another mechanism in CRC development, and how biomarkers of colonic mucosal barrier function may provide avenues for disease, prevention and detection.